Autologous platelet‐rich plasma therapy for pattern hair loss: A systematic review. (26th August 2019) - Dervishi, Gezim; Liu, Haibo; Peternel, Sandra; Labeit, Alexander; Peinemann, Frank
Abstract: Background: Androgenetic alopecia (male pattern and female pattern hair loss) is characterized by thinning of the scalp hair. Intradermal injection of autologous platelet‐rich plasma (PRP) might have an effect on hair regrowth. Aims: The aim was to evaluate efficacy and safety of platelet‐rich plasma compared to placebo or no treatment in people with pattern hair loss. Patients/Methods: We searched the databases CENTRAL and MEDLINE on December 24, 2018 and included randomized controlled trials (RCTs). Primary outcomes were mean change of hair density from baseline and serious treatment‐related adverse events. Secondary outcome was mean change of hair thickness from baseline. Time point of outcome assessment was 6 months after start of treatment. Results: We identified 13 relevant randomized controlled trials with 356 randomized (343 analyzed) people or half‐head areas who received PRP in a simple parallel or half‐head design. The pooled data of seven studies (171 analyzed people or half‐head areas) were favorable in the PRP group on hair density. We estimated a mean difference from baseline of 30.35 associated with a wide 95% confidence interval (1.77‐58.93), a considerable heterogeneity (I 2 = 100%), and unclear risk of bias in most of the studies. Regarding hair thickness, data were also favorable in the PRP group, but these data were limited to a single study. We did not identify serious treatment‐related adverse events. Conclusion: The results of seven RCTs indicated that autologous platelet‐rich plasma was associated with an increase of hair density when compared to placebo.